1970
DOI: 10.1085/jgp.56.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Uptake of Sodium at the Outer Surface of the Frog Skin

Abstract: A combination of the methods described by Schultz et al. (6) and by Ussing and Zerahn (9) was used to measure directly the unidirectional uptake of sodium from the outside solution into the frog skin, under shortcircuit conditions. The sodium uptake was determined at six sodium concentrations ranging from 3.4 to 114 m. NaCI was replaced by choline chloride in the solutions bathing both sides of the skin. Sodium uptake is not a linear function of sodium concentration but appears to be composed of two component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 18 publications
7
93
1
Order By: Relevance
“…In this process, Na+ enters the cell via an apical membrane channel and is extruded by the basolateral membrane Na+-K+ ATPase. The frog skin (26,27), toad urinary bladder (28), rabbit urinary bladder (29), and the turtle colon (30) kidney distal nephron, and particularly the collecting duct, also possess an electrogenic Na+ transport system but the processes are more complex. For example, the rat distal nephron has an electroneutral NaCl cotransport system in addition to an electrogenic system (31).…”
Section: Resultsmentioning
confidence: 99%
“…In this process, Na+ enters the cell via an apical membrane channel and is extruded by the basolateral membrane Na+-K+ ATPase. The frog skin (26,27), toad urinary bladder (28), rabbit urinary bladder (29), and the turtle colon (30) kidney distal nephron, and particularly the collecting duct, also possess an electrogenic Na+ transport system but the processes are more complex. For example, the rat distal nephron has an electroneutral NaCl cotransport system in addition to an electrogenic system (31).…”
Section: Resultsmentioning
confidence: 99%
“…While the values of most parameters discussed in this paper were measured by several authors in both species, comparative values of JOT are not available because the technical possibility of a direct measurement of JOT is relatively new Biber & Curran, 1970), and (2) the technique for the evaluation of JOT used in this paper required a large exposed area (8-9 cm2) and this makes it impossible to obtain two pieces of M. CEREIJIDO AND C. A. ROTUNNO white abdominal skin for paired experiments out of the same L. ocellatus. R. pipiens are available in sizes as large as 4-5 in.…”
Section: Na Influxmentioning
confidence: 99%
“…There is a hyperbolic relationship between sodium influx (or at least that component of influx associated with sodium transport) and sodium concentration, indicative of a saturable phenomenon. At a given sodium concentration antidiuretic hormone increases influx, whereas amiloride inhibits influx (Rotunno, Villalonga, Fernandez & Cereijido, 1970;Biber & Curran, 1970;Cereijido & Rotunno, 1971;Biber, 1971;Ferguson & Smith, 1972; Moreno, Reisin, Rodriguez-Boulan, Rotunno & Cereijido, 1973;Biber & Cruz, 1973;Erlij & Smith, 1973;Biber & Sanders, 1973). One of the sources cited above (Biber & Sanders, 1973) is of particular interest since it was shown that the extent of sodium influx at a given sodium concentration can be influenced by the transepithelial potential.…”
Section: Introductionmentioning
confidence: 99%